2019
DOI: 10.1136/bmjopen-2019-032444
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to implement the family doctor contracting services in China: findings from a qualitative study

Abstract: ObjectiveTo identify the facilitators and barriers to implement family doctor contracting services in China by using Consolidated Framework for Implementation Research (CFIR) to shed new light on establishing family doctor systems in developing countries.DesignA qualitative study conducted from June to August 2017 using semistructured interview guides for focus group discussions (FGDs) and individual interviews. CFIR was used to guide data coding, data analysis and reporting of findings.Setting19 primary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 19 publications
1
91
0
Order By: Relevance
“…The hierarchical medical system emphasizes the importance of a clear division of health care roles and responsibilities for different levels of hospitals, and highlights the significance of taking strategies to encourage the utilization of primary care [ 8 ]. The implementation of the family physician-contracted service (FPCs) is one of the key actions, which improve people’s access to primary health care, minimize the unfair distribution of medical resources and improve the health of community residents [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchical medical system emphasizes the importance of a clear division of health care roles and responsibilities for different levels of hospitals, and highlights the significance of taking strategies to encourage the utilization of primary care [ 8 ]. The implementation of the family physician-contracted service (FPCs) is one of the key actions, which improve people’s access to primary health care, minimize the unfair distribution of medical resources and improve the health of community residents [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The public health policy of China has always put emphasis on rural areas and grassroot communities, 6 as the quality and quantity of GPs are critical to meet the basic medical and public health needs of rural populations. 7 Although rural doctors in China undertake the duties of GPs, some receive no formal training in general practice. 8 Therefore, the government of China has aimed to improve the general practice literacy of rural doctors through various CME programs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that existing contract services were superficial and deceptive, pursued only quantity, were not accepted by patients, and lacked guarantee [7,8]. The contract rate was low, under 30%, in rural areas [9]. To solve these problems and improve the implementation of family doctor contract services, numerous studies have explored the factors that influence patients' willingness to utilize the contract services.…”
Section: Introductionmentioning
confidence: 99%